PENGARUH SUBSTITUSI TEPUNG LABU KUNING TERHADAP KUALITAS MI BASAH - OVIYANTI, LINA; Faridah, Anni; Kasmita, Kasmita (Journal of Home Economics and Tourism, 2014)
The use ofpumpkinflourasafoodingredientinfooddiversification, as onealternative towheat.This study aimedtoanalyzethe effect of differentcomposition ofpumpkinflouras much as0%, 40%, 50% and60% of the quality oftexture, color, aromaandtaste ofwet noodles. This research is anexperimentusinga completely randomized designwiththreereplications,the number ofpanelists30 people. The results showedthat thesubstitution of40% showsthe results ofthe best views oftexture, color, aromaandflavor. Keywords: Pumpkin, Wet Noodle, Quality, Substitution